Investigation of multi-drug resistant Candida auris using species-specific molecular markers in immunocompromised patients from a tertiary care hospital in Quetta, Pakistan - Hira Ejaz; Muhammad Mushtaq; Shereen Khan; Nasir Azim; Abrar Hussain; Kaleemullah Kakar; Muhammad Zubair Khan; Ayisha Hafeez; Syed Moeezullah (PLoS ONE, 2025)
Introduction Candida auris is an emerging multidrug-resistant pathogen responsible for nosocomial infections worldwide, characterized by high mortality rates and significant challenges in detection due to frequent misidentification. Classified by the WHO as a pathogen of critical importance since it exhibits resistance to multiple antifungal agents, particularly fluconazole, and is highly transmissible in healthcare settings. Conventional detection methods often lack the accuracy required for effective infection control. This study aimed to conduct inferential and molecular analyses of C. auris and other yeast species infecting immunocompromised patients in the Special and Intensive Care Units (SCU and ICU) of a tertiary care hospital in Quetta, Pakistan. In this region, C. auris remains rarely studied and is frequently misdiagnosed by clinical staff due to limited awareness and diagnostic challenges. Notably, no prior research has been conducted on C. auris in Quetta. The study also sought to develop reliable diagnostic methods suitable for resource-limited settings, addressing a critical gap in healthcare infrastructure. Materials and methods Samples (150 each) from the ear, axilla, groin, and saliva of SCU/ICU patients were collected and processed on yeast malt agar, with preliminary identification using Brilliance Candida Agar (BCA) and CHROMagar Candida Plus (CCP). Advanced techniques, including PCR amplification of ITS regions, DNA sequencing, RFLP with Msp1, MALDI-TOF, Vitek 2, and species-specific primers, were used for identification. Antifungal susceptibility to fluconazole, amphotericin B, and voriconazole were also assessed. Results The culture test revealed that 42.6% samples were positive for yeast infections. In addition to detecting Candida auris in 4 cultures, chromogenic media identified 6 other Candida species: C. albicans, C. dubliniensis, C. glabrata, C. krusei, C. parapsilosis, and C. tropicalis. Further validation through advanced techniques, including molecular diagnostics and MALDI-TOF, enabled the identification of additional species: C. famata, C. kefyr, C. lusitaniae, and Meyerozyma (Candida) guilliermondii. Out of all identified yeast species C. dubliniensis was the most common, followed by C. albicans and C. tropicalis, with the highest infection rates observed in saliva samples. Antifungal Susceptibility Tests (AST) revealed that C. auris isolates were resistant to Fluconazole, Amphotericin B, and Voriconazole, highlighting multidrug resistance. This study represents the first report of novel multidrug-resistant C. auris from Quetta, Pakistan, indicating that C. auris is prevalent among ICU and SCU patients. Novel species specific primers targeting phospholipase B, topoisomerase II, CDR and 18s genes were designed in our laboratory and not previously reported in earlier studies, proved highly effective for the rapid identification of Candida species. The established protocol using these primers is recommended for implementation in resource-limited laboratory settings. The statistical analysis demonstrated significant correlations between Candida species infection (dependent variable) and several independent factors (variables) emphasizing the importance of targeted diagnostics and intervention strategies.